1978
DOI: 10.1111/j.1651-2227.1978.tb17816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Anaemia on the Placenta and the Newborn Infant

Abstract: Foetal birthweight, placental morphometry and maternal, cord blood and placental haemoglobin and iron levels were studied in 69 anaemic mothers (haemoglobin less than 110 g/l) and 16 mothers without anaemia (haemoglobin greater than or equal to 110 g/l). The birthweight, placental weight and number of placental cotyledons were significantly reduced in the severely anaemic mothers (haemoglobin less than or equal to 60 g/l) and had direct relationships with the maternal haemoglobin levels. However, placental vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 9 publications
(4 reference statements)
3
41
0
1
Order By: Relevance
“…Esta falta de relación obedecía mas bien a problemas metodológicos. Estudios realizados en países en los que la deficiencia de hierro en la embarazada es alta, han mostrado una asociación entre la nutrición de hierro materna y los niveles de ferritina sérica en el cordón [34][35][36][37] . Los niveles de ferritina de lactantes menores hijos de madres que recibieron suplementación con hierro durante el embarazo son significativamente más elevados que los de hijos de madres no suplementadas con hierro 33 .…”
Section: Consecuencias De La Deficiencia De Hierro En El Embarazounclassified
“…Esta falta de relación obedecía mas bien a problemas metodológicos. Estudios realizados en países en los que la deficiencia de hierro en la embarazada es alta, han mostrado una asociación entre la nutrición de hierro materna y los niveles de ferritina sérica en el cordón [34][35][36][37] . Los niveles de ferritina de lactantes menores hijos de madres que recibieron suplementación con hierro durante el embarazo son significativamente más elevados que los de hijos de madres no suplementadas con hierro 33 .…”
Section: Consecuencias De La Deficiencia De Hierro En El Embarazounclassified
“…In the present study, mean number of cotyledons in control group was 17.46±1.04, while that in test group was 13±1.9; indicating that number of cotyledons was significantly decreased in anemic mothers. Significant reduction was reported by Singla et al [25] and it was found to be directly due to severe anemia. Once again, findings of the present study regarding the number of cotyledons are at par with the previous studies.…”
Section: Fig 5: Placental Volumementioning
confidence: 77%
“…The cause can be attributed to reduction in the 'exchange-surface' of placenta [34] , directly related to the maternal hemoglobin level and hence anemia. To be precise, the low levels of placental iron or cord serum iron in severely anemic mothers suggests that fetal intake of iron is directly proportional to the level of available iron in the maternal blood [25] . The placental weight is the single most important factor reflecting fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed significantly lower cord hemoglobin levels in the infants of severely anemic women compared with infants born to iron-sufficient mothers. [109][110][111][112] Likewise, diet-induced maternal anemia in rhesus monkeys caused a significant reduction in hemoglobin, mean corpuscular volume, and bone marrow colony-forming units in the newborns, 113 suggesting a limited capacity of the placenta to support fetal erythroid needs in the face of severe maternal deficiency.…”
Section: Regulation Of Iron Transport Across the Placentamentioning
confidence: 99%